ANALISIS KEUNTUNGAN USAHATANI PADI (Oryza sativa L ) SAWAH PASANG SURUT DI DESA TAMBAK KARYA KECAMATAN KURAU KABUPATEN TANAH LAUT PROVINSI KALIMANTAN SELATAN - Wasdiyanta; Zuraida (Chlorophyl, 2022)
This study aims to determine the cultivation method and the total cost, revenue and profits of tidal rice farming. The sampling method used a simple random method on a population of 150 Ciherang rice farmers taken 20% to 30 respondents. The cultivation method is carried out in a traditional way. Total cost Rp. 10,107,154.99, total revenue Rp. 787,850,000.00 or an average of Rp. 26,261,666,67/farmer and the total profit is Rp. 484,635,350.30 or an average of Rp. 16,154,511.68/farmer/ planting season